An outcome of emergency vascular surgery performed by General Surgeons; our experience in a university hospital of Pakistan and can they substitute vascular surgeons? - Mohammad Sohail Asghar; Ahmad Siddique Ammar; Sumbal Naz; Anwar, Jamal; Ameer Afzal; Mohammad Musaab (Journal of the Pakistan Medical Association, 2022)
Objective: To measure the outcome of emergency vascular surgery performed by general surgeons, and to identify preventable causes of mortality. Method: The retrospective study was conducted at the General Surgery Department of Mayo Hospital, King Edward Medical University, Lahore, Pakistan, and comprised data between January 2014 and May 2019 related to cases regardless of age and gender that required emergency vascular surgery after diagnosis by a consultant surgeon at the surgical emergency. The cases were analysed from admission till discharge. Data was analysed using SPSS 20. Results: Of the 135 cases, 127(94%) were males. The overall mean age was 28.8+11.5 years (range: 14-63 years). Mean duration of hospital stay was 11+3.92 days (range: 4-22 days). Three major peripheral arteries injured were brachial 32(38.5%), popliteal 55(40.7%) and femoral 20(20.7%), with more than half with complete transection 75(55.6%). Vascular repairs done were primary anastomosis 45(33.3%), reverse saphenous vein graft 68(50.4%), embolectomy 4(3%) and amputation 18(13.3%). Limb salvage rate and mortality was 101(74.8%) and 6(4.4%), respectively. Complications occurred in 38(28.1%) cases, with 24(18%) wound infections and 9(6.7%) myonecrosis. Factors leading to poor outcome/complications were Glasgow Coma Scale score <12 (p=0.01), referred case (p=0.04), significant bleeding (p=0.004), haemoglobin <9 at presentation (p=0.001), bone fracture (p=0.01), involvement of lower limb (p=0.003) and late presentation (p=0.003). Conclusion: Late presentation in hospital was the major modifiable factor improvement of which could lead to better outcome, apart from the early and proper surgical intervention. Key Words: Vascular surgery, Artery repair, Venous graft, Vascular anastomosis.